2017
DOI: 10.1007/s00167-017-4680-x
|View full text |Cite
|
Sign up to set email alerts
|

Large correction in opening wedge high tibial osteotomy with resultant joint-line obliquity induces excessive shear stress on the articular cartilage

Abstract: The effects of HTO for varus knee deformity on the amount/distribution of stresses in the articular cartilage were analysed using a 3D finite element model. It was shown that joint-line obliquity of more than 5° induced excessive shear stress in the tibial articular cartilage. A large amount of correction in OWHTO with a resultant joint-line obliquity of 5° or more may induce detrimental stress to the articular cartilage. Double-level osteotomy should be considered as a surgical option in this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
190
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(203 citation statements)
references
References 42 publications
4
190
0
9
Order By: Relevance
“…Non-anatomic knee joint obliquity can cause excessive shear force on the articular cartilage. When the obliquity angle is 5 , the shear force in the medial compartment elevate to almost twice as high as the normal knee [10]. The force value becomes even higher as the obliquity angle increases.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Non-anatomic knee joint obliquity can cause excessive shear force on the articular cartilage. When the obliquity angle is 5 , the shear force in the medial compartment elevate to almost twice as high as the normal knee [10]. The force value becomes even higher as the obliquity angle increases.…”
Section: Discussionmentioning
confidence: 95%
“…A positive value represented that the medial articular surface is higher than the lateral surface. A ≧ 5 KJLO was de ned as a high-degree KJLO [10]. (Fig.…”
Section: Radiological Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,18 It is important to consider the obliquity of the joint line for the preoperative planning of HTO. 24,25 According to Schuster et al, the postoperative MPTA should be less than 95 degrees to avoid the obliquity of the joint line. 26 Our post-planning MPTAs were close to or even bigger than 95 degrees; the cause of this phenomenon is that we included patients with normal preoperative MPTA; the mean preoperative MPTA was 85.44 AE 2.55 degrees (►Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of metaphysical varus deformity was suggested to be a reliable prognostic factor after OWHTO. 6 Nakayama et al 21 showed that joint-line obliquity of more than 5-degree induced excessive shear stress in the tibial articular cartilage in finite element model analysis. Heijens et al 22 concluded that the MPTA reflected the static osseous component, and the JLCA, which was changed by soft tissue stretching, reflected the dynamic component as a result of realignment.…”
Section: Discussionmentioning
confidence: 99%